Toward an Ecological-Political Understanding of Migration from Tunisia: Exploring the Role of Energy Policies in Southern Ecosystems' Desertification - Arianna Poletti (REMHU: Revista Interdisciplinar da Mobilidade Humana)
Abstract This article examines the phenomenon of people in movement by considering the human and environmental impact of export-oriented energy policies through the case study of Southern Tunisia’s territory and communities. The analysis aims to interrogate the neglected link between the social-economic context of territories hosting impactful energy infrastructures, the resulting control over ‘human’ and ‘natural’ ecosystems that inhabit these territories, and their consequent abandonment, leading to migration. The research sheds light on how coercive measures and oppressive policies prioritize maximal resource extraction, depriving local citizens of their agency. Consequently, communities no longer resist the establishment of energy infrastructure, leading to the abandonment of their land and the loss of control over natural resources. By adopting a political ecology approach, this article aims to expand the category of climate migrants arguing that the economic criterion cannot be omitted nor separated from the climatic one. The case study of Southern Tunisia exemplifies the dynamics of precarity and structural poverty underlying migration peculiar to territories where, paradoxically, high value-added resources such as oil and gas as well as renewable energy are extracted and exported.